Polyadenylation of Vesicular Stomatitis Virus mRNA - Ehrenfeld, Ellie (1974)
Vesicular stomatitis virus (VSV) mRNA isolated from infected cell polysomes contains polyadenylic acid [poly(A)] sequences. Detergent-activated purified virions in vitro can transcribe complementary RNA, which has sedimentation properties similar to mRNA, and this RNA also contains poly(A) sequences. Digestion of virion RNA with U2 RNase under conditions where hydrolysis is specific for purine linkages leaves no sequences of polyuridylic acid corresponding in length to the poly(A) on the transcripts. Growth of infectious virus is not inhibited by 3-deoxyadenosine (cordycepin) under conditions in which it inhibits polyadenylation of cellular mRNA. The virus-specific mRNA produced in the presence of cordycepin has poly(A) sequences of the same size distribution as that synthesized in the absence of cordycepin.